2023
DOI: 10.1186/s41927-023-00327-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in research: a review of practical resources for young investigators

Abstract: Patient and public involvement (PPI) in every aspect of research will add valuable insights from patients’ experiences, help to explore barriers and facilitators to their compliance/adherence to assessment and treatment methods, bring meaningful outcomes that could meet their expectations, needs and preferences, reduce health care costs, and improve dissemination of research findings. It is essential to ensure competence of the research team by capacity building with available resources on PPI. This review sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…This PPI work aimed to provide preliminary information on how women engaged with humorous digital PFMT nudges on Instagram as part of a social media campaign to promote PFMT. The Guidance for Reporting Involvement of Patients and the Public Version 2 short form checklist was used to enhance the quality, transparency and consistency of reporting the study 4,19 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This PPI work aimed to provide preliminary information on how women engaged with humorous digital PFMT nudges on Instagram as part of a social media campaign to promote PFMT. The Guidance for Reporting Involvement of Patients and the Public Version 2 short form checklist was used to enhance the quality, transparency and consistency of reporting the study 4,19 …”
Section: Methodsmentioning
confidence: 99%
“…2 Studies have shown PPI improves research quality, relevance and impact by increasing the likelihood of research translating into practice and improving population health 3 by providing insights into the patient experience and highlighting barriers and facilitators to treatment adherence. 4 A means of involving the public in research is through contribution to important decisions in the research process, such as the design of novel interventions. 3 PPI is vital in women's health research because it engages a historically underserved population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last 4 weeks of the study, the use of the powered mobility device will be free, and the child might use the device when he or his family decide so. Follow-up period will be carried out using Photovoice (29) for capturing photographs under the basis of Participatory Action Research (PAR) (30) and the Public and Patient Involved (PPI) (31,32) approach in the research. To do this, the families will be trained to capture high-quality photos during their children's routine moments while using the device.…”
Section: Intervention Featuresmentioning
confidence: 99%
“…The 31 articles published in this Article collection can be categorized into several PPI-related themes spanning all stages of research—patient education/empowerment/engagement/perspectives, research priority setting, co-created design, improving outcomes, patient-led design, harnessing clinical care frameworks, community/patient advisory boards and quality evaluation. First, Arumugam et al [ 1 ] provided a brief review introducing the background of PPI along with practical considerations, referencing frameworks, guidance and tools for researchers to get started—most notably, a helpful table was created with links to resources as an additional file for help integrating PPI throughout the research lifecycle.…”
Section: Introductionmentioning
confidence: 99%